1999
DOI: 10.1046/j.1365-2516.1999.0050s1005.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options in the management of articular contractures in haemophiliacs

Abstract: Haemophilic contracture is seen most commonly as an equinus deformity of the ankle, or at the knee or elbow in the form of a flexion deformity. Treatment options are varied, and decision-making is based on the degree of the contracture, its chronicity, the presence of articular subluxation, the patient's ability to participate in treatment, and the available medical facilities. The treatments available fall into four categories: physiotherapy, orthotics, corrective devices, and surgical procedures. Treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…In previous studies, we have found that osteotomy of hemophilic knee and hip joints did not necessarily prevent further destruction (Wallny et al 2002(Wallny et al , 2003. Furthermore, untreated or only non-operatively managed equinus deformities also show progressive arthropathy (Rodriguez-Merchan 1999). It therefore seems that with or without surgical management, deterioration of the ankle joint is inevitable-and is most likely not a result of Achilles tendon lengthening.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, we have found that osteotomy of hemophilic knee and hip joints did not necessarily prevent further destruction (Wallny et al 2002(Wallny et al , 2003. Furthermore, untreated or only non-operatively managed equinus deformities also show progressive arthropathy (Rodriguez-Merchan 1999). It therefore seems that with or without surgical management, deterioration of the ankle joint is inevitable-and is most likely not a result of Achilles tendon lengthening.…”
Section: Discussionmentioning
confidence: 96%
“…Casting often results in a reduction in the available ROM due to prolonged immobilisation (Rodriguez-Merchan, 1999). Disuse atrophy or a reduction in the strength of the thigh muscles is one of the commonest complications of this procedure.…”
Section: Plaster Of Paris Serial Casting or Wedge Castingmentioning
confidence: 99%
“…Patients with skin traction or reverse dynamic traction are often restricted to bed until the traction is applied (Rodriguez-Merchan, 1999).…”
Section: Skin Tractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement therapy with recombinant factor VIII or IX is the first and essential step in the treatment of hemarthrosis [5]. Physical therapy interventions have a fundamental and an efficient role in the rehabilitation of these patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%